Hypoxia Enhances Endothelial Intercellular Adhesion Molecule 1 Protein Level Through Upregulation of Arginase Type II and Mitochondrial Oxidative Stress - Liang, Xiujie; Arullampalam, Prakash; Yang, Zhihong; Ming, Xiu-Fen (Frontiers in Physiology, 2019)
Hypoxia plays a crucial role in the pathogenesis of cardiovascular diseases. Mitochondrial enzyme arginase type II (Arg-II) is reported to lead to endothelial dysfunction and enhance the expression of endothelial inflammatory adhesion molecules such as intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1). In this study, we investigate the role of Arg-II in hypoxia-induced endothelial activation and the potential underlying mechanisms. Exposure of the human endothelial cells to hypoxia induced a time-dependent increase in Arg-II, HIF1α, HIF2α, and ICAM-1 protein level, whereas no change in the protein level of VCAM-1 and E-selectin was observed. Similar effects were obtained in cells treated with a hypoxia mimetic Dimethyloxaloylglycine (DMOG). Silencing HIF1α, but not HIF2α, reversed hypoxia-induced upregulation of Arg-II. Moreover, silencing Arg-II prevented the ICAM-1 upregulation induced by hypoxia or DMOG. Furthermore, the endothelial cells incubated under hypoxic condition or treated with DMOG or hypoxia enhanced monocyte adhesion, which was inhibited by silencing Arg-II. Lastly, silencing Arg-II prevented hypoxia-induced mitochondrial superoxide production in endothelial cells, and hypoxia-induced ICAM-1 upregulation was reversed by mitochondrial electron transport inhibitor rotenone. These data demonstrate that hypoxia enhances ICAM-1 protein level and monocyte-endothelial interaction through HIF1α-mediated increase in Arg-II protein level on leading to increased mitochondrial reactive oxygen species production. These effects of hypoxia on endothelial cells may play a key role in cardiovascular diseases. Our results suggest that Arg-II could be a promising therapeutic target to prevent hypoxia-induced vascular damage/dysfunction.